Enhancing Writing Skills in Persuasive Texts Through a Pancasila-Integrated Snakes and Ladders Game Framework - Fauzan, Muhammad; Yuniawan, Tommi; Pristiwati, Rahayu (The Journal of Educational Development, 2024)
The integration of educational games in academic settings has consistently improved student engagement and retention of knowledge, particularly in writing education. However, the use of these games to embed national values such as Indonesia's Pancasila within persuasive writing curricula remains underexplored. This study aimed to develop and assess the effectiveness of an Android-based Snakes and Ladders game that integrates Pancasila values to enhance persuasive writing skills among junior high school students. Employing a structured framework, the research was conducted with 70 students. A comprehensive needs analysis was performed using a survey to evaluate students' experiences with existing educational tools and their receptiveness to the game-based learning model. Statistical analysis of survey responses confirmed the reliability of the assessment tools and helped in refining the game design. The results demonstrated significant improvements in students' persuasive writing skills and their engagement with the educational content, confirming the game's effectiveness in integrating academic and cultural education. This study introduces a novel approach by using an educational game to merge persuasive writing education with the inculcation of national values, providing a dual focus that enhances both academic abilities and cultural identity. The findings contribute to educational technology and curriculum development by offering a scalable model that can be adapted in diverse educational settings to merge cultural education with academic learning. This approach has significant implications for regions prioritizing the integration of cultural values into education, suggesting a path forward for educational reform that harmonizes tradition with technological advancements.